Problematyka oznaczania wytworów generatywnej sztucznej inteligencji w świetle polskiej ustawy o zwalczaniu nieuczciwej konkurencji - Jasińska, Katarzyna (PRAWO i WIĘŹ, 2025)
The paper is devoted to the issue of marking the products of generative artificial intelligence in the light of the Polish Act on Combating Unfair Competition. The possibility of qualifying the fact of concealing the creation of a given product/provision of a given service as a result of the exclusive action of AI or its cooperation with a human, as well as attributing the „authorship” of such a product to a human, as one of the torts of unfair competition, under Article 10 and Article 3, paragraph 1 of the Act on Combating Unfair Competition, has been analyzed. In the context of Article 10, the issue of not only misleading marking but also misleading lack of marking of goods/services was analysed.